Influence of plasma with finite pressure on magnetic configuration of torsatron U-3M - Pashnev, V.K.; Burchenko, P.Ya.; Kulaga, A.Ye.; Lozin, A.V.; Mironov, Yu.K.; Petrushenya, A.A.; Romanov, V.S.; Sitnikov, D.A.; Sorokovoy, Ed.L.; Tsybenko, S.A.; Zamanov, N.V. (Вопросы атомной науки и техники, 2009)
Series of experiments on generation of mode with high β (up to about 1.3%) in torsatron U-3M were performed
using nitrogen as working gas. The dependence of average β from input power was obtained. The average plasma radii
in modes with various β were determined. The estimation of rotational transformation angle was done in view of
presence of the plasma in device. На торсатроні У-3М проведено серію експериментів по створенню режиму з високим β (до 1.3%) з
використанням азоту в якості робочого газу. Отримано залежність середнього β від потужності, що вводиться.
Було визначено середній радіус плазми в режимах з різним β. Оцінка кута обертального перетворення була
зроблена з урахуванням наявності плазми в установці. На торсатроне У-3М проведена серия экспериментов по созданию режима с высоким β (до 1.3%) с
использованием азота в качестве рабочего газа. Получена зависимость среднего β от вводимой мощности. Был
определён средний радиус плазмы в режимах с различным β. Оценка угла врщательного преобразования была
сделана с учетом наличия плазмы в установке